2022
DOI: 10.1021/acs.jafc.2c04708
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Novel Pyrazol-5-yl-benzamide Derivatives Containing Oxazole Group as Potential Succinate Dehydrogenase Inhibitors

Abstract: A series of pyrazol-5-yl-benzamide derivatives containing the oxazole group were designed and synthesized as potential SDH inhibitors. According to the results of the bioassays, most target compounds displayed moderate-to-excellent in vitro antifungal activities against Valsa mali, Sclerotinia scleotiorum, Alternaria alternata, and Botrytis cinerea. Among them, compounds C13, C14, and C16 exhibited more excellently inhibitory activities against S. sclerotiorum than boscalid (EC50 = 0.96 mg/L), with EC50 values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The detailed method of SEM for this assay was performed according to the literature. , In brief, the mycelia dishes (5 mm in diameter) were inoculated on PDA medium plates containing no ingredient (negative control) and compounds 7d and 12b (concentration = 1 μg/mL) cultured at 25 °C for 2 days. The effect of compounds 7d and 12b on the mycelial morphology of R.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed method of SEM for this assay was performed according to the literature. , In brief, the mycelia dishes (5 mm in diameter) were inoculated on PDA medium plates containing no ingredient (negative control) and compounds 7d and 12b (concentration = 1 μg/mL) cultured at 25 °C for 2 days. The effect of compounds 7d and 12b on the mycelial morphology of R.…”
Section: Methodsmentioning
confidence: 99%
“…The SEM method was used in this study, based on relevant literature. [37][38][39] Mycelia dishes with a diameter of 5 mm were inoculated on PDA medium plates and cultured at 25 °C for 2 days with 5 k, Boscalid (concentration = 1 μg/mL) and negative control. The effect of 5 k and Boscalid on the mycelial morphology of R. solani was observed and studied using SEM.…”
Section: Scanning Electron Microscopy (Sem) Analysismentioning
confidence: 99%
“…In our previous work, our group designed and synthesized a series of novel pyrazol-5-yl-benzamide derivatives containing the oxazole group as SDH inhibitors. The biological activity test results showed that some compounds exhibited excellent antifungal activities.…”
Section: Introductionmentioning
confidence: 99%